Fish biodiversity and water quality of Batiano, Iloio and Sibalom Rivers. - Baylon, Vanessa Karla (UPHSI, 2007)
An investigation was conducted to identify the species of fish collected in the rivers of Batiano (Villa, Iloilo), Iloilo (Iloilo City), and Sibalom (Tigbauan, Iloilo). Water quality of the water such as dissolved oxygen (DO), temperature, pH, salinity, and turbidity were also determined.